I am number four - Lore, Pittacus (Lore, Pittacus. Lorien legacies, 2011)
In rural Ohio, friendships and a beautiful girl prove distracting to a fifteen-year-old who has hidden on Earth for ten years waiting to develop the Legacies, or powers, he will need to rejoin the other six surviving Garde members and fight the Mogadorians who destroyed their planet, Lorien.